The Presence of the Peroneus Tertius Muscle in Thai People - Kunnika Chatyingmongkol (Siriraj Medical Journal, 2004)
The peroneus tertius is a small partially separated portion of the extensor digitorum longus, as its fifth tendon, but has an important role in locomotion and in the evolution of human beings. It supports and stabilizes the longitudinal arches of the foot while standing and locomotion during bipedalism. In particular, it assists in everting the foot, which is a characteristically human movement. This study was performed by dissecting 247 legs from 144 cadavers. In these cadavers, we found a high percentage of the presence of this muscle, the peroneus tertius, (95.55%). The absence of the muscle was rare, only in 4.45%. Regarding the muscle size, which was calibrated at the ankle joint and compared with the common tendon of the extensor digitorum longus at the same area, the proportion was very large at 34.77% in the right leg and 39.55% in the left leg. The results of this study emphasized and clarified the important role of this muscle.